Teaching Mathematics for Social Justice: The Challenges and the Prospects in The Ghanaian Senior High Schools - Amoako Atta, Seth; Bonyah, Ebenezer (Manunggal Halim Jaya, 2023)
The study aimed to explore the prospects and challenges of teaching mathematics for social justice at Ghanaian Senior High Schools. A non-random sample of seven (7) respondents, including two experienced mathematics educators and five Senior High School students, were interviewed and analysed quantitatively using thematic analysis. The analysis revealed seven themes: individual differences, students' mathematics interests, participatory lessons, extracurriculars, non-interactive teaching, technology use and cultural diversity. These thematic findings are related to technical, practical, and emancipatory knowledge constituent interests in schools and Ghanaian social, cultural, and historical settings. A teacher should utilise egalitarian pedagogy so that the students will gain practical and emancipatory skills.